The Resilience of Ungku Kali Practices as Marriage Guardian in Kurai Taji, Padang Pariaman Regency Maslahah Perspective - Ali Ibrahim; Hamda Sulfinadia; Ikhwan Ikhwan; Jurna Petri Roszi (Jurnal Ilmiah Al-Syir'ah, 2023)
This paper focuses on the resilience of Ungku Kali's practice as a marriage guardian or transfer of lineage guardian to Ungku Kali. The Ungku Kali referred to in this study, is someone appointed by both husband-and-wife candidates to carry out the marriage and acts as a marriage guardian. The research questions from this paper are, first, what is the position and practice of Ungku Kali as a marriage guardian in Kurai Taji, Padang Pariaman Regency? Second, why does Ungku Kali’s practice as a marriage guardian persist today? The primary data of this study came from interviews with thirteen informants, consisting of six couples getting married, three Ungku Kali people, and four local people. After collecting the data, they were classified according to the existing themes and analyzed with the resilience theory. The study results found that Ungku Kali's position in Kurai Taji is as a trustee in the religious field or a respected Nagari cleric in society. As for the Ungku Kali practice using the facilities of the Surau Korong Lubuk Ipuh as a place of practice assisted by Apak Labai as the marbot at the Surau Korong Lubuk Ipuh, all the requirements are conveyed by this Apak Labai. Second, the reason for the resilience of the Ungku Kali practice until now is due to the resilience of culture, the resilience of economic factors, the resilience of the need factor, and the resilience of social factors; both Ungku Kali service users and Ungku Kali itself.